Lesser Than Equal? - Saumya Uma (African Journal of Gender and Religion (AJGR))
In India, Hindu family law is often touted as a progressive and gender-just law that ought to be emulated and extended to minority religious communities through a common civil code. Against this backdrop, the present article examines the question of whether Hindu family law in India adequately protects women’s rights and, if law reform is required, what should be the  factors guiding it. The article further analyses the status of women within Hindu family law in India from the time of the country’s independence and the law reform measures that have led to advancement in women’s equality rights in recent decades as well as discriminatory provisions that continue to persist through a historical, legal and feminist lens. It argues that further reforms to Hindu family law must be undertaken to realize women’s equality rights, albeit within the larger framework of constitutional norms and international human rights standards, rather than an interpretation/re-interpretation of Hindu religious texts based on dubious claims of a “glorious past.” This includes recognition of trans* and queer relationships within the folds of Hindu law. Moreover, the article argues in favor of applying feminist discourses on formal and substantive equality to the Uniform Civil Code debate to ensure plural family laws are gender-just.